Răspuns :
a + b = 10
ab = 15
(a + b) ^2 = a^2 + 2ab + b^2 = 100
a^2 + b^2 = 100 - 2x15 = 100 - 30
a^2 + b^2 = 70
ab = 15
(a + b) ^2 = a^2 + 2ab + b^2 = 100
a^2 + b^2 = 100 - 2x15 = 100 - 30
a^2 + b^2 = 70
a+b=10
a·b=15
Utilizăm formula de calcul prescurtat:
[tex] (a+b)^{2}= a^{2}+2ab+ b^{2} [/tex]
Înlocuim ceea ce cunoaștem în formulă și obținem:
[tex] 10^{2} = a^{2}+2*15+ b^{2} \\ 100= a^{2}+30+ b^{2} \\ 100-30= a^{2}+ b^{2} \\ a^{2}+ b^{2} =70.[/tex]
a·b=15
Utilizăm formula de calcul prescurtat:
[tex] (a+b)^{2}= a^{2}+2ab+ b^{2} [/tex]
Înlocuim ceea ce cunoaștem în formulă și obținem:
[tex] 10^{2} = a^{2}+2*15+ b^{2} \\ 100= a^{2}+30+ b^{2} \\ 100-30= a^{2}+ b^{2} \\ a^{2}+ b^{2} =70.[/tex]